2014
DOI: 10.1002/jbm.b.33258
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage assessment of low shrinkage composites using micro-computed tomography

Abstract: Both low shrinkage composites showed less volumetric polymerization contraction than the regular composite. The use of dental adhesive decreased the total volumetric shrinkage for all evaluated composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 40 publications
3
40
0
2
Order By: Relevance
“…Studies reported that shrinkage may occur at deeper areas of restorations 21) , while other investigation found that changes in the bottom of the cavity were delayed when compared to the surfaces closer to the light source 33) . Clinically the bottom and lateral shrinkage generated (gap formation), represented by 3D deformation of the uncured composite, are relevant once it may result in post-operative sensitivity, internal and marginal gaps 24) . In this study, volumetric shrinkage was primarily detected at the occlusal surface, little at bottom and almost inexistent at sides.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies reported that shrinkage may occur at deeper areas of restorations 21) , while other investigation found that changes in the bottom of the cavity were delayed when compared to the surfaces closer to the light source 33) . Clinically the bottom and lateral shrinkage generated (gap formation), represented by 3D deformation of the uncured composite, are relevant once it may result in post-operative sensitivity, internal and marginal gaps 24) . In this study, volumetric shrinkage was primarily detected at the occlusal surface, little at bottom and almost inexistent at sides.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been shown to depict locations of composite shrinkage when the substrate adherent was uniform, revealing gap formation regions and regions of potential interfacial failure 24) . Reducing the light intensity and modifying the polymerization technique with Soft-start mode did not significantly change the volumetric polymerization shrinkage and neither affect the degree of conversion achieved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations